Are anatomical landmark measurements accurate for predicting endotracheal tube depth? - Mangar, Devanand; Sprenker, Collin Jurgen; Karlnoski, Rachel Anne; McDonough, John P; Dodson, Robert K; Brashears, Bill H; Downes, Katheryne L; Camporesi, Enrico M (International Journal of Advanced Nursing Studies, 2013)
Background: A traditional method for depth of intubation in adult patients is taping the endotracheal tube (ETT) at the upper incisors a distance of 21 or 23 cm for women and men respectively (21/23 method). A novel “topographical” measurement for estimating proper intubation depth has been suggested as a better depth predictor compared to the 21/23 method.   Objectives: To compare the 21/23 method to topographical measurements. Methods: 100 ASA physical status I-II patients scheduled for elective surgery were enrolled. The 21/23 method was initially utilized for intubation and the ETT tip to carina distance was then fiberoptically measured. Anatomical (topographical) measurements were then obtained from each patient by adding the distance from the corner of the mouth to the mandibular angle to the distance from the mandibular angle to the center of the sternal notch and were recorded as the topographical intubation depth. Both measurements were assessed for percentage of ETTs that fell outside of our desired tip to carina range of 2-4 cm. Results: After the 21/23 method, 29% of ETTs fell outside our desired tip to carina range compared to 47% of ETTs with the topographical method (p=0.010). No correlation was found between the topographical measurements and airway length (upper incisors to vocal cords) (r=0.248). Conclusions: Topographical measurements were not re-confirmed as an accurate intubation method and were found to be less reliable than the 21/23 method. We maintain that regardless of ETT insertion method utilized, the gold standard to ensure accurate ETT placement is fiberoptic inspection.